1996
DOI: 10.1017/s0268416000003325
|View full text |Cite
|
Sign up to set email alerts
|

Last years of life: changes in the living and working arrangements of elderly people in Amsterdam in the second half of the nineteenth century

Abstract: Dans cet article, on cherche à définir le degré d'indépendance des personnes âgées qui résident à Amsterdam dans la seconde moitié du XIXe siècle. On examine la structure des ménages et le degré d'activité des personnes âgées dans trois groupes sociaux. A partir des registres de population, il apparaît que presque la moitié des personnes âgées vivent dans des ménages où leurs enfants sont présents, la plupart co-résident avec des enfants non mariés. On a comparé les formes de résidence au décès, avec les forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Even in an urban setting, and possibly more so than in the countryside, the attitude for a long-lasting intergenerational relationship was a basic tenet of familial and social relations, which explained the frequency of extended households arrangements (Seccombe 1993;Goody 1998: 89-90;Stavenuiter 1996). Not unexpectedly, it was the daughters who were primarily appointed with it (Derosas 2003;on daughters' role, see Skinner 1997: 68).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in an urban setting, and possibly more so than in the countryside, the attitude for a long-lasting intergenerational relationship was a basic tenet of familial and social relations, which explained the frequency of extended households arrangements (Seccombe 1993;Goody 1998: 89-90;Stavenuiter 1996). Not unexpectedly, it was the daughters who were primarily appointed with it (Derosas 2003;on daughters' role, see Skinner 1997: 68).…”
Section: Resultsmentioning
confidence: 99%
“…It was marriage that gave men full membership of the community, and secured respectability, (relative) independence, and control over their own households to women (Laslett 1983b: 12, 101;Sabean 1990: 61). Correspondingly, the lowest layers of society were predominantly constituted by unmarried adults and elders (Wall 2007;Stavenuiter 1996;Crossick and Haupt 1995: 101;Sabean 1990: 456;Laslett 1988;Hufton 1984), whose presence was often perceived as a source of embarrassment and moral concern by local authorities (Bennet and Froide 1999;Froide 2005;Anderson 1984;McCants 1999;Ogilvie 1997: 64;Sabean 1990: 456;Zannini and Gazzi 2004;Accati 1998;Palazzi 1990;Filippini 1983). The disadvantaged condition of the unmarried was also common to Asian societies (Skinner 1997: 83), and is sadly persisting in contemporary affluent economies (see e.g.…”
Section: From Constraints To Coercion: Marriage and Social Reproductionmentioning
confidence: 99%
“…These living arrangements could be observed throughout the nineteenth century and in the early twentieth century. 7 The Swedish conditions, however, do not seem to correspond with studies of the elderly's living conditions in urban areas in the Netherlands 8 and the United States. These studies showed high rates of intergenerational co-residence in the late nineteenth and early twentieth centuries, underlining the great importance of family networks in urban areas.…”
Section: Introductionmentioning
confidence: 91%